RANCANG BANGUN SISTEM PELAYANAN SKRIPSI PADA UIN SULTAN AJI MUHAMMAD IDRIS SAMARINDA - Basrie, Basrie; Sugiyono, Sugiyono (Journal of Social Computer and Religiosity (SCORE), 2023)
The purpose of this study is to examine the application of science in the fields of technology and information in the form of online student services at Sultan Aji Muhammad Idris Smarinda University. The system development method used in this study is waterfall, with the following stages1) Requirements and definition; 2) System and Software Design; 3) Implementation and Unit Testing; 4) Integration and System Testing; and 5) Operations and Maintenance. The technology used to build the system is Codeigniter and LTE The expected results in this study are the establishment of a thesis service system for students in accordance with academic services, as well as making it easier for academics and lecturers to perform services.